Analysis of lymph node spread and its prognostic significance in ampullary adenocarcinoma: A retrospective study - Zhang, Zheng-Yun; Guan, Jiao; Wang, Xin-Ping; Hao, Di-Si; Zhou, Zun-Qiang (Frontiers in Surgery, 2022)
Background Nodal status is a vital prognostic factor for ampullary adenocarcinoma. This study was designed to evaluate the clinical significance of the positive nodes in this disease. Methods Data from 110 patients who underwent curative pancreatoduodenectomy for ampullary adenocarcinoma between January 2007 and December 2018 were retrospectively collected and analyzed. Results The median number of lymph nodes per patient was 32 (20–46). Metastatic lymph nodes were found in 84 (76.4%) patients. In patients with positive nodules, the most commonly involved nodes were the #13 (80.1%) and #17 (78.6%) nodes, followed by #12 (69.0%) and #8 nodes (57.1%). Patients with 3–4 positive nodes among #13, #17, #12, and #8 had lower survival rates than those with 0 or 1–2 nodes. Conclusion Ampullary adenocarcinoma commonly spreads to #13, #17, #12, and #8 lymph nodes. These nodes affected the patients' survival rates dramatically.